Population study of thrombophilic markers and pharmacogenetic markers of warfarin prevalence in Bosnia and Herzegovina - Ašić, Adna (Croat Med J, 2019)
AIM: To investigate the prevalence of common genetic variants that can serve as markers of thrombophilia and warfarin pharmacogenetics in Bosnia and Herzegovina. METHODS: The study was performed between August and October 2017 on 130 healthy unrelated adult volunteers from Bosnian-Herzegovinian population sample. The prevalence of the following genetic variants was determined: F5 c.1601G>A (factor V Leiden), F2 c.*97G>A (factor II or prothrombin mutation), F13A1 (factor XIII) c.103G>T, MTHFR (methylenetetrahydrofolate reductase) c.665C>T and c.1286A>C, as well as PAI-1 (plasminogen activator inhibitor 1) c.-816A>G and c.-844G>A as markers of thrombophilia risk, and *2 and *3 alleles of CYP2C9 (cytochrome P450 2C9) and five variants of VKORC1 (vitamin K epoxide reductase complex subunit 1) as markers of warfarin pharmacogenetics. DNA was isolated from buccal swabs using salting out method, while genotyping was performed using matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry. RESULTS: Minor allele frequencies for two main thrombophilia risk factors, F5 c.1601G>A and F2 c.*97G>A were 0.023 and 0.008, respectively. Combined data for the markers of warfarin pharmacogenetics imply that 57.4% study participants can be expected to metabolize warfarin at an extensive, 40.3% at intermediate, and 2.3% at a poor rate. CONCLUSION: This study reports the first extensive population genetic data for thrombophilia and warfarin pharmacogenetic markers in Bosnia and Herzegovina. Allele frequencies of genetic variants are within the general average for European populations, and their presence implies the necessity of introduction of personalized medicine in warfarin-mediated antithrombotic therapy.